Social protection and Venezuelan migration in Latin America and the Caribbean in the context of COVID-19 - Anna Carolina Machado; Nurt Palomo; Mónica Rubio; Gerardo Escaroz; Rodolfo Beazley; Ana Solórzano; Giulia Baldi (International Policy Centre for Inclusive Growth (IPC-IG), 2021)
The COVID-19 pandemic represents an enormous challenge for all countries due to its public health consequences and socio-economic effects on families. In this difficult context, the Latin America and the Caribbean region is facing the largest displacement in its recent history. This migrant population faces various risks, whether linked to the migration process or their migratory status, or others that were aggravated by the health emergency. This Research Report summarises a report by the IPC-IG, UNICEF LACRO and WFP, which presents an analysis of the inclusion of the Venezuelan migrant population in social protection as part of the response to the pandemic emergency in nine countries in Latin America and the Caribbean.
Keywords: 330; COVID-19 pandemic; social protection; migration